Effects of felling intensities on Gigantochloa ligulata bamboo for improvement of shoot production - Mohamed, Azmy; Maziun, Mohamed Azuan; Hassan, Affendy; Wahab, Razak (Universiti Putra Malaysia Press, 2013)
Gigantochloa ligulata (buluh tumpat) is considered as one of the commercial bamboo species in Malaysia. Owing to its demand as food, especially in the northern part of the country and since it is relevant to improve production of bamboo shoots, a study on the effects of felling intensity as one of the silvicultural treatments on G. ligulata bamboo was conducted at Taman Wetland, in Putrajaya, Malaysia. Three culm felling intensities were applied for four months in 2005. The felling intensities of 0% (control), 30% and 60% were applied twice every two months within the four-month period. There were six replications done and 3kg of organic fertilizer was also applied. The number of shoots sprouted and their weights, including culm number, were monitored. The clump expansion pattern of selected treatment clumps were observed for dead and new shoots sprouted. The shoots were tagged and recorded every week. A shoot, which grew up to 30cm and from the ground, was considered as a shoot. The weights of the shoots with sheath were recorded on a weekly basis. The distribution pattern of the shoot sprouting was also observed. It was found that 30% felling intensity gave extra four shoots, as compared to other intensities, including the control with a value of 0.009 for both the treatments at 0.05 probability level.